The Quality Of Blooming Steamed Sponge Cake With Different Steamer Materials And Steaming Times - Khairani, Mifta Zhafira; Elida, Elida; Kasmita, Kasmita; Anggraini, Ezi (Jurnal Pendidikan Tata Boga dan Teknologi, 2025)
Steamed sponge cake is a popular cake product due to its fluffy texture, soft crumb, and distinctive sweet taste. One of the important factors that determine the success of steamed sponge cake is the material of the steaming equipment and the steaming time. This study aims to determine the effect of steaming equipment materials (bamboo, aluminum, and stainless steel) and steaming time (15, 20, and 25 minutes) on the quality of steamed sponge cake. The study used an experimental method with a 3×3 factorial design and three replicates. Organoleptic tests were conducted by five trained panelists on aspects of volume, four-segment fluffy shape, and texture (moist, soft, and finely porous). The results of the analysis showed that the steaming tool material had a significant effect on all quality aspects (p < 0.05), while the steaming time and the interaction between the two had no significant effect (p > 0.05). The highest average quality scores were obtained for the aluminum steamer, namely volume 3.33, four-segment shape 3.00, and neat shape 3.07. The Fcount value for the steamer factor was 6.41 for volume, 61.00 for four-segment fluffy shape, and 21.80 for neat shape, which was greater than the Ftable (3.31) at the 5% level. Thus, it can be concluded that the steamer material has a significant effect on the quality of steamed sponge cake, where aluminum steamers produce products with expanded volume, perfect four-segment fluffy shape, and soft and moist texture that are most preferred by panelists.